Los pictogramas y el lenguaje oral en niños de 3 a 4 años de la Unidad Educativa José Ángel Palacio de la ciudad de Loja en el periodo 2023-2024 - Armijos Andrade, Karen Lisseth (2024)
The development of oral language is essential in the lives of human beings as it is an efficient form of communication between individuals, enabling their interaction and the development of cognitive skills, fundamental for optimal personal and social functioning. Therefore, the present research aimed to determine how pictograms improve the oral language of children aged 3 to 4 years at José Ángel Palacio Educational Unit in the city of Loja, for the period 2023-2024. A non-experimental research design was used to collect unmanipulated data on the independent variable and analyze the dependent variable bibliographically. The mixed approach collected and analyzed both qualitative and quantitative data, and the descriptive scope allowed for the description of definitions, benefits, characteristics, stages, components, and strategies of the variables under study. Additionally, inductive-deductive and analytical-synthetic methods were used to collect and analyze information for the construction of the theoretical framework. For the collection of variables, the observation technique was employed, and the instrument used was the Navarra PLON-R Test, to determine the level of oral language development applied to 14 children aged 3 to 4 years. The results showed that 71.42% are delayed, presenting difficulties in interpreting images, creating sentences, participating in activities that involve the use of graphic symbols, as well as formulating and pronouncing words correctly. Considering the detected problem, a pedagogical proposal was designed entitled: “Discover, Play, and Learn through fun activities to strengthen your language”, concluding that the application of pictograms is a didactic tool with significant pedagogical influence, contributing to vocabulary enrichment, facilitating both comprehension and verbal expression, thus enabling fluent communication. Keywords: communication, cognitive skills, oral language, early childhood education, pictograms, vocabulary.